The Assumption of Unlimited Human Wants (AUHW) in Islamic Economics - Mohd Zulkifli Muhammad; Hanudin Amin; Dzulkifli Mukhtar; Shah Iskandar Fahmie Ramlee; Noormariana Mohd Din (2020)
Purpose: This study examines the assumption of unlimited human wants in Islamic economics where tasawur is brought into play. Design/methodology/approach: Drawing from the analytical approach, the present study presents new concepts of unlimited human wants. The assumpion of unlimited human wants (AUHW) was taken by Islamic economists and therefore altered and assimilated with Islamic elements so that it can be known as the assumption of Islamic economics. The question is, does the assumption of AUHW accept in Islamic economics? If fits, what are the assumptions of unlimited human wants parallel with Islamic tasawur? The data employed were drawn from Library research. The contents and textual analyses were employed to achieve this purpose. Findings: This study found out that the assumption of AUHW was parallel with tasawur and for that, they are suitable for Islamic economics. Research limitations/implications: This study examines a new approach to measure unlimited human wants in Islamic context. Our contributions are confined to this area – human wants. Our study also limits its perspective on the general context of tasawur. Future works can provide specific perspectives on unlimited human wants covering different geographies. Practical implications: This study provides a new parameter for Muslims to manager their resources according to Islam. Originality/value: This study introduces a new measure of addressing unlimited human wants among Muslims.